UPAYA MENINGKATKAN KREATIVITAS ANAK USIA 3-4 TAHUN MELALUI MEDIA POPING (POHON PISANG) DI PPT MADANI KLAMPIS NGASEM SURABAYA - SUJATI . (MOTORIC, 2020)
The current phenomenon in the education system only emphasizes cognitive abilities. In connection with this, the researchers conducted research by developing the creativity of children in the 3-4 year age group at PPT Madani. The purpose of this study is to increase the creativity of students using POPING (banana tree) media.The type of research used was the design of Kemmis and Mc Taggart and carried out in two cycles. The data collection technique used was observation to determine the fluency and originality aspects and interviews to find out flexibility and elaboration. Data analysis techniques in this study are qualitative descriptive and quantitative description of percentages.The improvement results are shown in cycle I and cycle II are known to increase from 50% to 85%. It can be concluded that students' creativity in making toys from POPING (banana tree) is very high. Keywords: creativity, POPING (banana tree)